Los principios configuradores del tipo social y la sociedad anónima en la Ley General de Sociedades, ¿una sociedad intuitu pecuniae? - Herrada Bazán, Víctor (Revista de Derecho, 2019)
From a dogmatic perspective, the public limited company is viewed as an intuitu pecuniae corporate. Although this view is taken until today for most of the Peruvian doctrine and jurisprudence, a review of our corporate law allow us to discard that character from this corporate type. This has major implications for the admissibility of certain conditions in statutes, not expressly provided in Peruvian law, insofar as that they are not incompatible with its legal status. This paper defends the non-essentiality of intuitu pecuniae characteristic of public limited companies, by treating about essential elements of corporate forms in Peruvian law.